The COMBI (Communication for Behavioural Impact)program in the prevention and control of dengue - the Hulu Langat experience - S Rozhan,; M Jamsiah,; A. Rahimah,; K.T. Ang, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Background: The COMBI concept is a novel approach by the WHO to control communicable diseases which are influenced by community behaviour. The Ministry of Health is currently evaluating its use against dengue in selected areas throughout Malaysia. COMBI doctrine differs from previous dengue campaigns. It acknowledges that the factors contributing to dengue proliferation may differ between areas. Factors for a given area are analysed, then a single precise behavioural goal to overcome those problems is formulated. To inculcate this behavioural change, the target community is subjected to an intensive campaign using Integrated Marketing Communication techniques adapted from the advertising industry, particularly involving volunteers from the community itself. Methodology: In Selangor the pilot project was implemented in Section 3 and Section 4 of Bandar Baru Bangi, in the district of Hulu Langat. Here, Aedes breeding was found to occur mainly in water containers of semi permanent nature (eg. ‘kolah’, aquatic plant jars, flower pot bases etc). A total of 172 volunteers were recruited to disperse the message of “Suluh – Suluh, Basuh - Basuh” whilst distributing leaflets and flashlights to 2666 homes. Residents were instructed to illuminate such water containers twice weekly and scrub any containers found to contain larvae. The program commenced on 23/5/2004 and lasted 16 weeks. Results : During this period, the initial Aedes Index of 5 was reduced to 0.96 while combined cases of Dengue Fever / Dengue Haemorraghic Fever in Sections 3 and 4 reported to the Hulu Langat District Health Office also dropped to 1 (unconfirmed). Conclusion : The COMBI approach in Hulu Langat successfully demonstrated that correct problem identification synergized with community engagement can potentially reduce Aedes proliferation and dengue morbidity.